Assessment of High-Risk Factors in Pregnancy and Their Association with Demographic Variables Among Women in Urban and Rural Communities of West Bengal. - Shreyasi Hui,; Soma Das,; Shubhra Chowdhury,; Krishma Jindal,; Divya, (The Bioscan, 2026)
A descriptive study was conducted to assess the high-risk factors of pregnancy among women attending selected outpatient department of urban and rural community, West Bengal with the objectives to identify the high-risk factors of pregnancy and its association with selected demographic variables.